Adsorption of cadmium from wastewater with activated carbons derived from pig fur biowaste: A comparative study of in-situ and ex-situ activation routes - Henry Oghenero Orugba; Jude Ebieladoh Sinebe; Jeremiah Lekwuwa Chukwuneke; Victor Ikenna Okoro; Chukwudi Louis Enyi; Okwuchukwu Innocent Ani (Heliyon, 2024)
The environmental challenges associated with cadmium contamination in wastewater have necessitated the development of high-performing activated carbons (ACs) for effective wastewater treatment. Adsorption capacity depends on both the surface area and the adsorption-active functional groups developed on the adsorbent's surface during activation. Proper manipulation of key process variables using the appropriate activation route produces highly efficient and economically viable ACs. This research investigates the viability of pig fur biowaste as a novel precursor for activated carbons using two distinct activation methods—in-situ and ex-situ. Using a central composite design (CCD) of the Response Surface Methodology (RSM), the study systematically examines the effects of impregnation ratio, carbonization temperature, and carbonization time on the cadmium adsorption capacities of the resulting ACs. The optimal conditions for in-situ activation were found to be 691 °C, 175.11 min, and an impregnation ratio of 1.784 g/g, resulting in a cadmium adsorption capacity of 91.57 %. For ex-situ activation, the optimal conditions were 468.8 °C, 80.81 min, and an impregnation ratio of 2.915 g/g, which achieved a higher cadmium adsorption capacity of 91.21 %. Both types of activated carbons maintained high efficiency after five regeneration cycles, indicating they are suitable for long-term applications requiring repeated regeneration. Although both methods produced ACs with comparable cadmium removal efficiency, the ex-situ activation route proved to be more economically viable due to its lower temperature and shorter processing time. This study demonstrates the potential of pig fur biowaste as a sustainable and underutilized resource for AC production and highlights the ex-situ activation route as the more cost-effective approach for producing high-performance adsorbents.